Intensive Family Preservation Services to prevent out-of-home placement of children: A systematic review and meta-analysis - Bezeczky, Z; El-Banna, A; Petrou, S; Kemp, A; Scourfield, J; Forrester, D; Nurmatov, UB (Elsevier, 2020)
Background Intensive Family Preservation Services (IFPS) are in-home crisis intervention services designed to help families with children at imminent risk of out-of-home placement.